Excessive use of force : one mother's struggle against police brutality and misconduct - Prater, Loretta P. (Rowman & Littlefield, 2018)
Police brutality and misconduct have been under the microscope for the last several years. Loretta Prater confronts the far-reaching consequences of police brutality through the personal case of her son, numerous examples of other cases, and a review of related research.